A PENGARUH PEMBERIAN SUMPLEMEN TTD, PERSALINAN DI FASKES DAN PENIMBANGAN BALITA TERHADAP ANGKA STUNTING PADA 6 PROVINSI DENGAN KASUS TERTINGGI DI INDONESIA TAHUN 2016 - 2024 - Abdi Tanjung; Bonaraja Purba; Runggu Sihombing; Sam Deva Nasra Sinulingga (Jurnal Stunting Pesisir dan Aplikasinya, 2026)
This study aims to analyze the effects of iron-folic acid supplement (IFAS) distribution, delivery at health facilities, and toddler weighing on stunting rates in the six provinces with the highest stunting rates in Indonesia from 2016 to 2024. The study employs a quantitative approach using panel data analysis based on secondary data from the Indonesian Ministry of Health. The analysis was conducted using E-Views 12 with the Fixed Effects Model (FEM) as the best-fitting model based on the Chow and Hausman tests. The results indicate that the administration of TTD and weighing of infants have a negative and significant effect on stunting, while childbirth at health facilities has a positive and significant effect. Simultaneously, all three variables significantly influence the prevalence of stunting. These findings suggest that accelerating the reduction of stunting requires integrated health and nutrition interventions from the prenatal, perinatal, to postnatal phases within the framework of the First 1,000 Days of Life (HPK).